Preclinical and clinical advances in dual‐target chimeric antigen receptor therapy for hematological malignancies. Issue 4 (21st February 2021) - Guo, Zhenling; Tu, Sanfang; Yu, Siyao; Wu, Liufang; Pan, Wanying; Chang, Ning; Zhou, Xuan; Song, Chaoyang; Li, Yuhua; He, Yanjie
Abstract: In recent years, the excellent curative effect of CD19‐specific chimeric antigen receptor (CAR) T‐cell therapy has brought hope to patients with relapsing or refractory B‐cell hematological malignancies, however relapse after CAR T‐cell infusion has hindered the widespread clinical application of this immunotherapy and targeted antigen‐negative relapse has caused widespread concern. Consequently, strategies for increasing targeted antigens have been created. In addition to the most widely applied target, namely CD19, researchers have further explored the possibility of other targets, such as CD20, CD22, CD33, and CD123, and have tested a series of combination antigen CAR T‐cell therapies. Here, we summarize the current preclinical and clinical studies of dual‐target CAR T cells. Abstract : CD19‐specific chimeric antigen receptor (CAR) T‐cell therapy has excellent efficacy in patients with relapsed or refractory B‐cell hematological malignancies, however antigen loss after single‐target CAR T‐cell infusion hinders the clinical application of this immunotherapy. Researchers have proposed a dual‐target chimeric antigen receptor‐armed T cell (CART) strategy for more comprehensive tumor coverage. Here we summarize current preclinical and clinical studies on dual‐target CAR T cells.